PENGARUH NILAI BUDAYA NASIONAL INDONESIA TERHADAP PREFERENSI GAYA MANAJEMEN KONFLIK (Studi Pada Karyawan Tendik FISIP Undip) - Ayu Puspitasari, Dyah; Mas’ud, Fuad (Faculty of Economics and Business Diponegoro University, 2018)
There are several studies on conflict management styles applied to countries in Western and non-Western cultures, for example Turkey, India and China. Although many studies have examined conflict management style preferences in several countries in Asia, there have been no studies examining the influence of Indonesian national culture on conflict management style preferences. Thus the conflict management style is not yet known what is the preference of the Indonesian people. The research conducted by Ma (2010) states that Turks who apply collectivism value choose a style of collaboration and competition to overcome conflict. Whereas conflict management style which is the preference of Chinese society is a style of compromise, while the style of competition conflict management becomes a conflict management style that is avoided Kirkbride, Sara, and Westwood (1986). The purpose of this research is to know the influence of Indonesian national cultural values on conflict management style preferences.This research was conducted at the Faculty of Social and Political Sciences Diponegoro University of Semarang. The number of samples used were 65 respondents by census method. Data analysis method used in this research is simple regression analysis and multiple regression using SPSS.The results of this study indicate that the style of conflict management are more likely to use are compromising style and collaborating style, while the style of competing is a style of conflict management is rarely applied. In addition, the values of collectivism have different effects on the management style of employee FISIP Undip, such as the value of cooperation and acceptance the role in the group leads to the style of collaborating style preferences, and the value of cooperation and acceptance the role in the group leads to the style of compromising style preferences.